The University Students’ Anxiety in Learning English Grammar - Maryati Salmiah; Fitriyani Fitriyani (English Education : English Journal for Teaching and Learning, 2022)
This study had purposes to find out students’ anxiety types, the reason why they got the anxiety and their suggestions for the lecturer who teaches English grammar to release their students’ anxiety. To reach the purposes, a qualitative method was used. Twenty anxious of first year students at university were chosen to be participants of the research. Those students were interviewed by fifteen questions. Most students said that lack knowledge of English Grammar made them anxious in learning the subject. The students suggest the lecturer identified students’ anxiety before the lesson started; creating fun, communicative and less formal class; and overcoming students’ problems in learning Grammar. It is concluded that every students faced anxiety in learning grammar but the lecturer could minimize it.